THE QUANTIFYING OF BIOMASSA AT OIL PALM PLANTATION IN LANGKAT, NORTH SUMATERA - Muhdi (Jurnal Pertanian Tropik, 2015)
Quantifying oil palm plantation contribution to global carbon budgets is needed. Biomass variation of oilpalm plantation practices through allometric models that can be used to asses oil palm plantation. Theobjectives of this research were to find the biomass variation of oil palm plantation in Langkat, NorthSumatera. The research was done in two steps. Firstly, data collecting was at oil palm plantation. The secondstep was analyzed biomass in a laboratory. Measurement of parameters is done by 9 (nine) permanentsample plots (PCP) with line block method in 5 years, 10 years and 15 years. The size of the plots was 20 m x 20m (400 m2) that distance to another plot was 10 m x 10 m (100 m2) used random sampling. This researchfound that the models of biomass in oil palm plantation was W = 0.00597D1.000Hbp1.142.